Digital transformation: Learning from Italy's public administration*. Issue 2 (November 2020) - Datta, Pratim; Walker, Laurie; Amarilli, Fabrizio
Companies and governments have embraced digital transformation as the elixir of the 21st century. But what impedes digital transformation? This case study article is based on data gathered from field research with the Italian Parliament and the Digital Transformation High Commissioner's Office in the Ministry of the Interior. The case surfaces the context, challenges, and solutions for large-scale public administration digital transformation. The case study highlights how public administration digital transformation in a large democracy is never a technical but a sociotechnical solution. Successful digital transformation needs to understand, address, and change sociopolitical and sociotechnical mores that often define the culture. Underscoring this research is an analysis of digital transformation within the Italian public administration. Public administration encompasses all governmental and public services, including services provided by federal, regional (e.g. states and provinces), municipalities, and local agencies. The Italian public administration, with 60 million people, 8000 municipalities, and 22, 000 local administrations, highlights how a digital renaissance is a preface for innovative disruption challenges. The Digital Transformation case uses Italy as the backdrop and Team Digitale, a team of talented individuals embarked on building public administration efficiencies and rebooting Italy's digital innovation footprint, as the protagonist. For granularity, the case focuses on two digital transformation projects: ANPR, a unified public registry for all Italian residents, and PagoPA, a universal digital payment platform for public administration. This case surfaces the best practices and challenges faced when trying to tackle a mega-project across an entire economy. The case offers digital transformation recommendations, generalizable across any global democracy. The case analysis and recommendations bring to light how, contrary to private organizations, institutionalizing a disruptive innovation in a democratic country at a time of fiscal austerity highlights interesting decision-making issues and facets.